Mobile Money Adoption, Financial Inclusion, and Hedonism in SMEs - Maricar, Rezvanny; Paerah, Ambo; Hastuti, Puji (Journal of Business and Behavioural Entrepreneurship, 2024)
This study investigates the role of hedonism as a mediating variable in the relationship between mobile money adoption and financial inclusion among small and medium-sized enterprises (SMEs). The research explores how intrinsic satisfaction derived from using mobile money influences its adoption and impacts financial inclusion, providing a novel perspective on the psychological drivers of financial technology uptake. Utilizing a quantitative approach, data were collected from SMEs via standardized questionnaires, with relationships analyzed through regression and mediation techniques. The findings demonstrate that mobile money adoption significantly enhances financial inclusion, while hedonism partially mediates this relationship. Emotional satisfaction is shown to amplify the impact of mobile money adoption, underscoring the importance of user experience alongside functionality in driving technology adoption. The study concludes that incorporating hedonistic aspects into mobile money platforms can increase adoption rates and enhance the financial inclusion of SMEs. The results provide actionable insights for policymakers and service providers, highlighting the importance of user-centered design and tailored support. Future research should explore additional mediating factors and broader sample populations to further validate and expand on these findings.